2017
DOI: 10.1002/smll.201702985
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural Uniformity of Ordered Mesoporous Materials: Governing Lithium Storage Behaviors

Abstract: Nanostructured materials make a considerable impact on the performance of lithium-storage characteristics in terms of the energy density, power density, and cycle life. Direct experimental observation, by a comparison of controlled nanostructural uniformity of electrode materials, reveals that the lithium-storage behaviors of mesoporous MoO and CuO electrodes are linearly correlated with their nanostructural uniformity. Reversible capacities of mesoporous MoO and CuO electrodes with well-developed nanostructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 71 publications
(13 reference statements)
1
21
0
Order By: Relevance
“…S1a). In view of the highly interconnectivity microstructure of mesoporous channels on the KIT-6, a perfectly replicated nanocast material can be shaped [37][38][39][40]. Therefore, in order to obtain 3D ordered mesoporous cobalt ferrite phosphides, the immersion, calcination, phosphatization and etching processes were performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1a). In view of the highly interconnectivity microstructure of mesoporous channels on the KIT-6, a perfectly replicated nanocast material can be shaped [37][38][39][40]. Therefore, in order to obtain 3D ordered mesoporous cobalt ferrite phosphides, the immersion, calcination, phosphatization and etching processes were performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have focused on changing the composition and morphologies of active materials to overcome such issues and achieve a higher performance. [7][8][9][10][11][12] In contrast, the influence of polymorphs has been overlooked relative to that in the case of insertion-based electrode materials. Some studies have shown differences in the reactivity among various polymorphs of conversion-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…1C and D), the morphological structure and scanning electron micrograph showed the same subtle structure. 31 The complete structure of the silica replica is shown at a low magnication, and the dark and dense portion is the replica of the buttery wing cylindrical structure. The thin area between the obsessive walls is a replica of the cellular tissue, and at a higher magnication, this replication structure is more visible.…”
Section: Physical Characterization Of Hmsmentioning
confidence: 99%